IMPROVING ELEMENTARY SCHOOL TEACHERS’ COMPETENCE THROUGH THE NUMBERED HEAD TOGETHER METHOD AT SD OF TAMBANG SUB-DISTRICTS IN KAMPAR - Endang Purwanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper reports the improvement of teacher competence in a teacher work programme at Sub-Districts Tambang elementary school in Kampar through numbered head together method based on the background of the problem. Hence, the formulation of the problem is